Factors influencing recurrence following initial hepatectomy for colorectal liver metastases. Issue 10 (16th June 2016) - Hallet, J.; Sa Cunha, A.; Adam, R.; Goéré, D.; Bachellier, P.; Azoulay, D.; Ayav, A.; Grégoire, E.; Navarro, F.; Pessaux, P.; ,
Abstract: Background: Data on recurrence patterns following hepatectomy for colorectal liver metastases (CRLMs) and their impact on long‐term outcomes are limited in the setting of modern multimodal management. This study sought to characterize the patterns of, factors associated with, and survival impact of recurrence following initial hepatectomy for CRLMs. Methods: A retrospective cohort study of patients undergoing initial hepatectomy for CRLMs at 39 institutions (2006–2013) was conducted. Kaplan–Meier methods were used for survival analyses. Overall survival landmark analysis at 12 months after hepatectomy was performed to compare groups based on recurrence. Multivariable Cox and regression models were used to determine factors associated with recurrence. Results: Among 2320 patients, tumours recurred in 47·4 per cent at median of 10·1 (range 0–88) months; 89·1 per cent of recurrences developed within 3 years. Recurrence was intrahepatic in 46·2 per cent, extrahepatic in 31·8 per cent and combined intra/extrahepatic in 22·0 per cent. The 5‐year overall survival rate decreased from 74·3 (95 per cent c.i. 72·2 to 76·4) per cent without recurrence to 57·5 (55·0 to 60·0) per cent with recurrence (adjusted hazard ratio (HR) 3·08, 95 per cent c.i. 2·31 to 4·09). After adjusting for clinicopathological variables, prehepatectomy factors associated with increased risk of recurrence were node‐positive primary tumour (HR 1·27, 1·09 to 1·49), more than three liver metastases (HR 1·27, 1·06 to 1·52) and largest metastasis greater than 4 cm (HR 1·19; 1·01 to 1·43). Conclusion: Recurrence after CRLM resection remains common. Although overall survival is inferior with recurrence, excellent survival rates can still be achieved. Abstract : Survival acceptable despite recurrence